A quantitative assessment of air–sea heat flux trends from ERA5 since 1950 in the North Atlantic basin - Johannes Mayer (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Leopold Haimberger (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Michael Mayer (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna) (Earth System Dynamics, 2023)
The abstract is available here: https://uscholar.univie.ac.at/o:2067260 The abstract is available here: https://uscholar.univie.ac.at/o:2067260